Implementierung eines arithmetischen Kodierers in Java - Todtenbier, Christian

Fehlerangriffe auf spezielle Implementierungen von RSA - Ziegler, Max

Verkürzte Huffman-Codierung zur Codekompression - Lindner, Marvin

Tabellenbasierte arithmetische Kodierung bei allgemeinen Alphabeten - Ackermann, Marcel R.
Keywords: Diplomarbeit

Priority encoding transmission - Albanese, Andres; Blömer, Johannes; Edmonds, Jeff; Luby, Michael; Sudan, Madhu (IEEE Transactions on Information Theory)

Priority encoding transmission - Albanese, A.; Blömer, Johannes; Edmonds, J.; Luby, M.; Sudan, M. (Proceedings 35th Annual Symposium on Foundations of Computer Science)

Computing sums of radicals in polynomial time - Blömer, Johannes ([1991] Proceedings 32nd Annual Symposium of Foundations of Computer Science)

Denesting by Bounded Degree Radicals - Blömer, J. (Algorithmica)
Keywords: Applied Mathematics; Computer Science Applications; General Computer Science

Construction of Pseudorandom Functions - Fricke, Birgitta
Keywords: Diplomarbeit

Evaluierung und Implementierung eines vollständig verteilten RSA-Kryptographiesystems - Deveci, Deniz
Keywords: Diplomarbeit

The Weil-Pairing and Signature Schemes in Elliptic Curve Cryptography - Helbich, Anke
Keywords: Diplomarbeit

Timing Attacks for Cryptosystems based on Elliptic Curves - Schepers, Daniel
Keywords: Diplomarbeit

Implementierung und Evaluation eines MDS-Blockcodes mit unabhängigen Paritätssymbolen - Hoppe, Ulrich

Sicherheit und Anwendungen des Advanced Encryption Standard (AES) Rijndael - Krummel, Volker
Keywords: Diplomarbeit

Brauer Addition-Subtraction Chains - Otto, Martin
Keywords: Diplomarbeit

Closest Vectors, Successive Minima, and Dual HKZ-Bases of Lattices - Blömer, Johannes (Automata, Languages and Programming)

On the complexity of computing short linearly independent vectors and short bases in a lattice - Blömer, Johannes; Seifert, Jean-Pierre (Proceedings of the thirty-first annual ACM symposium on Theory of computing - STOC '99)

A lower bound for a class of graph based loss resilient codes - Blömer, Johannes; Trachsler, Beat (Technical report/Departement of Computer Science, ETH Zürich)

Denesting by bounded degree radicals - Blömer, Johannes (Algorithms — ESA '97)

The rank of sparse random matrices over finite fields - Blömer, Johannes; Karp, Richard; Welzl, Emo (Random Structures & Algorithms)
Keywords: random matrices; rank; finite fields

Approximate matching of polygonal shapes - Alt, Helmut; Behrends, Bernd; Blömer, Johannes (Annals of Mathematics and Artificial Intelligence)
For two given simple polygonsP, Q, the problem is to determine a rigid motionI ofQ giving the best possible match betweenP andQ, i.e. minimizing the Hausdorff distance betweenP andI(Q). Faster algorithms as the one for the general problem are obtained for special cases, namely thatI is restricted to translations or even to translations only in one specified direction. It turns out that determining pseudo-optimal solutions, i.e. ones that differ from the optimum by just a constant factor, can be done much more efficiently than determining optimal solutions. In the most general case, the algorithm for the pseudo-optimal solution is based on the surprising fact that for the optimal possible match betweenP and an imageI(Q) ofQ, the distance between the centroids of the edges of the convex hulls ofP andI(Q) is a constant multiple of the Hausdorff distance betweenP andI(Q). It is also shown that the Hausdorff distance between two polygons can be determined in timeO(n logn), wheren is the total number of vertices.

An XOR-based erasure-resilient coding scheme - Blömer, Johannes; Kalfane, Malik; Karp, Richard; Karpinski, Marek; Luby, Michael; Zuckerman, David

On Kummer theory and the number of roots of unity in radical extensions of Q - Blömer, Johannes

Simplifying Expressions Involving Radicals - Blömer, Johannes

Resemblance and symmetries of geometric patterns - Alt, Helmut; Blömer, Johannes (Data structures and efficient algorithms)

How to denest Ramanujan's nested radicals - Blömer, Johannes (Proceedings., 33rd Annual Symposium on Foundations of Computer Science)

Approximate matching of polygonal shapes (extended abstract) - Alt, Helmut; Behrends, Bernd; Blömer, Johannes (Proceedings of the seventh annual symposium on Computational geometry - SCG '91)

Computing sums of radicals in polynomial time - Blömer, Johannes (Proceedings 32nd Annual Symposium of Foundations of Computer Science)

Approximation of convex polygons - Alt, Helmut; Blömer, Johannes; Wagener, Hubert (Automata, Languages and Programming)